Sensing signal conditioning circuit design and analysis for emerging pressure sensing technology - Lim, John Jia Song (2017)
Advances made in the fields of material science and Micromechanical Systems (MEMS) have resulted in high performance MEMS devices that are used successfully as sensors. In the field of healthcare, emerging pressure sensor technologies have become of interest. Piezocapacitive, piezoelectric and piezoresistive sensors are some technologies used for pressure sensing for their excellent accuracy, sensitivity, resolution and miniaturization capability. In this research, the required performance of a radial pulse blood pressure sensor was characterized. Piezocapacitive, piezoelectric and piezoresistive sensors were then compared to review their operating principle, reliability, performance and robustness with respect to their ability to be used as a non-invasive radial pulse blood pressure sensor. For capacitive sensing, piezoelectric sensing and piezoresistive sensing, the technologies selected were the capacitive comb drive technology, PZT crystal and the highly doped semiconductor strain gage respectively. Using the high performance LTSPICE simulator, SPICE models were made based of the traits of the selected materials to simulate the electrical characteristics of the sensors. For each of these sensor electrical models, several signal conditioning circuit case studies were designed and analyzed. Charge mode amplifier and voltage mode amplifier circuits were built for piezoelectric sensors. Switched Capacitor based Capacitance to Voltage Converters and Capacitance to Digital Converters with a Successive Approximation Register (SAR) circuit were built for capacitive sensors. Finally, for the semiconductor piezoresistive strain gage, a Wheatstone bridge circuit used in conjunction with three different signal conditioning circuits were built: the op-amp subtractor, two op-amp INA and three op-amp INA. Transient response and frequency response simulations were then conducted in SPICE to analyze the performance of the circuit in response to a 100Hz sinusoidal signal, mimicking a 100Hz, 0 – 35KPa radial pulse signal. Based on the simulation results, the capacitive sensing and piezoresistive technologies were selected as good potential technologies to monitor radial blood pressure, though the final choice was made to use piezoresistive technology for its high performance and ease of use. The op-amp used to model the circuits were mostly ideal hence more investigation can be done in the future regarding the performance of these circuits with practical op amps.